Diagnosis of Helicobacter pylori infection by C-14 urea breath test in Ecuadorian population - Albán Loayza, Ronald W (2020)
Background: Early detection of Helicobacter pylori infection has become more relevant, with urea carbon-14 (C-14) breath test as one of the non-invasive diagnostic methods; however, it has not been proven in Ecuadorian population. Objective: To evaluate the sensitivity and specificity of the C-14 urea breath test to predict HP infection in the Ecuadorian population. Methods: : Study of diagnostic tests performed on patients who attended the outpatient gastroenterology service of the Hospital Teófilo Dávila in the city of Machala, in the period April 2018 to March 2019. The patients underwent an upper endoscopy of white light (WLE) with biopsies taken to investigate HP infection. In addition, a breath test with C-14 urea was performed to compare it with the biopsies results. Results: 78 patients with a mean age of 33.76±11.2 years were studied. The diagnosis of gastritis was confirmed through endoscopy and histopathology in 100% of the patients. The breath test with urea C-14 was positive in 47/78 (60.3%) patients. Evidence of HP infection was demonstrated in gastric biopsies from 50/78 (64.1%) patients. Sensitivity, specificity, PPV, NPV, and inter-rater reliability were 94%, 100%, 100%, 90%, 96%, and 92% (P <0.001), respectively. Conclusions: The C-14 urea breath test is a useful tool for predicting HP infection in the Ecuadorian population.